Energirealism i liberalismens fotspår! - Sundström,Fredrik (2023)
In recent years, both the price and the security of supply of plannable energy have changed drastically with increasing uncertainty regarding pricing and availability. The political will to ensure access to plannable and safe energy supply nationally has increased significantly during the same period. The study examines the question of whether the lack of cheap planable energy with the threat of energy poverty has led to the prevailing liberal view of energy supply being replaced by more realistic view of national energy supply? A comparative analysis shows that the energy policy in Sweden has gone from having a global liberal energy policy to having a more national realistic orientation to strengthen resilience in society and protect the own national robustness in domestic production and society. The congruence analysis shows that this adjustment has been driven by the events in our surrounding world and the currents in society, which confirms the study's purpose of proving that Sweden has moved towards a more realistic energy policy.
Keywords: Energipolitik; realism; liberalism